Distribution of nitrate-nitrogen in ground water and in some soils of Bihar - MISHRA, A K; SINGH, A K; SINHA, B K; PANDEYA, S B (The Indian Journal of Agricultural Sciences, 2013)
Â A study was conducted during 1996 at Pusa to evaluate the potential toxicity hazards of nitrate-N in ground water, the nitrate-N content was estimated in water samples from different sources like wells, hand pumps, ponds and tube wells located in areas receiving domestic sewage-sludge of low intensity (Pusa), municipal sewage-sludge (Patna), fertilizer factory effiuents (Barauni) and intensive chemical fertilization (Samastipur). The NO3-N contents or the soils of these areas were also estimated to evaluate the mobil ity of NO3-N. Most of the water samples’ collected from Barauni contained more than 10 mg/litre nitrate-N maki ng them unsafe tor potable use. Water samples from the wells situated in the city sludge disposal area of Patna was also judged unsafe. The water from tube wells and pumps was, however, safe for consumption. A good deal of nitrate-N enrichment was observed up to 90 cm soil depth in the cases where organic wastes were continuously disposed and nitrogenous fertilizers were applied in heavy doses. Implications of continuous disposal of organic wastes and application of high levels of N fertilizers in relation to nitrate-N of ground water contamination with nitrate-N is discussed.